EFEKTIFITAS PENGAWASAN DAN PENGENDALIAN PEREDARAN MINUMAN KERAS DENGAN PENGENAAN DENDA BERDASARKAN PERATURAN DAERAH KOTA BEKASI NOMOR 17 TAHUN 2009 - M Mawaddah; Dailami Firdaus; Damrah Mamang (Fakultas Hukum Universitas Islam As-Syafi'iyah, 2019)
This study aims to find out how effective the control and circulation of liquor in the city of Bekasi and the obstacles and constraints of the Bekasi city government in reducing violations of the circulation and sale of liquor in the city of Bekasi. There is a problem that will be studied in this study, namely how the role of the Bekasi city government and its staff in controlling the effectiveness of Bekasi city regulation number 17 of 2009 concerning the supervision and control of liquor circulation. This study uses empirical juridical research. The data sources used are primary data obtained through interviews with related sources in Bekasi city government, civil service police, police, industry and trade offices of the city of Bekasi, national and political health services, with the object of research, namely liquor control efforts in Bekasi city. This study uses primary law, namely the Republic of Indonesia Law Number 9 of 2015 concerning the Second Amendment to Law Number 23 of 2014 concerning Regional Government, Republic of Indonesia Government Regulation Number 6 of 2010 concerning Civil Service Police Unit, Minister of Trade Regulation Number 06 / M-DAG / PER / 1/2014 concerning control and supervision of the procurement, circulation and sale of alcoholic beverages, Regional Regulation Number 17 of 2009 concerning supervision and control of liquor circulation in the city of Bekasi. The results of the study show that the supervision efforts carried out by the relevant authorities such as the PP satpol,the police and the integrated team of the city of Bekasi are not effective due to the lack of law enforcement by the authorities. and related facilities that are still limited, the participation of the community that is still minimal and not yet concerned about the environment. Suggestions given from this study are that there is a need to change Bekasi Regional Regulation No. 17 of 2009 concerning regulations and control of liquor circulation, especially for sanctions contained in these regional regulations and the regional regulations can be accepted and adhered to by the people of Bekasi city.